1995
DOI: 10.2337/diacare.18.6.793
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence and Associated Features of Albuminuria in Koreans with NIDDM

Abstract: The prevalence of overt proteinuria in Korean NIDDM patients with a long diabetes duration was higher than that reported in Caucasians. Our data also suggest that the clinical meaning of microalbuminuria may be different based on the presence or the absence of retinopathy. Microalbuminuria in patients with retinopathy most probably would reflect diabetic nephropathy. In contrast, some recent-onset NIDDM patients with microalbuminuria in the absence of retinopathy had features of syndrome X.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
24
2

Year Published

1995
1995
2020
2020

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 38 publications
(27 citation statements)
references
References 25 publications
1
24
2
Order By: Relevance
“…85 The relationship between microalbuminuria (albuminuria) and clinical CVD has been confirmed in diverse racial/ethnic groups, including Koreans, American Indians, and Asian Indians. 81,86,87 Although the relationship is present in both type 1 and type 2 diabetes, the relationship is generally stronger in type 2 diabetes because of the older age of individuals with this disease. Framingham women 5209 CVD mortality Ϫ Ϫ ϩ indicates that the author concluded that proteinuria was an independent risk factor for the outcome after adjustment for all other risk factors; Ϫ, the author concluded that proteinuria was not an independent risk factor for the outcome after adjustment for all other risk factors.…”
Section: Cvd In Diabetic Kidney Diseasementioning
confidence: 99%
See 2 more Smart Citations
“…85 The relationship between microalbuminuria (albuminuria) and clinical CVD has been confirmed in diverse racial/ethnic groups, including Koreans, American Indians, and Asian Indians. 81,86,87 Although the relationship is present in both type 1 and type 2 diabetes, the relationship is generally stronger in type 2 diabetes because of the older age of individuals with this disease. Framingham women 5209 CVD mortality Ϫ Ϫ ϩ indicates that the author concluded that proteinuria was an independent risk factor for the outcome after adjustment for all other risk factors; Ϫ, the author concluded that proteinuria was not an independent risk factor for the outcome after adjustment for all other risk factors.…”
Section: Cvd In Diabetic Kidney Diseasementioning
confidence: 99%
“…Diabetic subjects with microalbuminuria also have an increased prevalence of dyslipidemia, poor glucose control, and increased blood pressure compared with diabetic patients without microalbuminuria. 80,81 There is a strong association between microalbuminuria (albuminuria) and CVD in cross-sectional analysis. This relationship has been found for surrogate measures, such as carotid intima-media thickness 82 and LVH, 83,84 and different clinical presentations of CVD, such as coronary artery disease 81,84 and peripheral vascular disease.…”
Section: Cvd In Diabetic Kidney Diseasementioning
confidence: 99%
See 1 more Smart Citation
“…The frequency of microalbuminuria in our group was 45.5%, with a tendency for increased systolic blood pressure, duration of the diabetes and hypertension In the stepwise multiple regression analysis, systolic blood pressure was the only variable that significantly influenced the rate of UAE. We did not observe a relation between HbA1c and microalbuminuria, sometimes reported 24,25 or not 26,27 in the literature. Possibly, transverse cohort studies, such as ours, are less likely to reveal the influence of glycemic control on the development of microalbuminuria.…”
Section: Arq Bras Cardiol Volume 73 (Nº 1) 1999mentioning
confidence: 66%
“…Although we cannot exclude a type 2 error, due to the size of the sample, other reports in the literature stress that CAD is associated mainly with macroalbuminuria and not microalbuminuria [24][25][26]33,35 . Possibly, this divergence with the literature, excluding data inherent to the studied population, is due to different methods and criteria for coronary disease and microalbuminuria diagnoses.…”
Section: Arq Bras Cardiol Volume 73 (Nº 1) 1999mentioning
confidence: 99%